1989
DOI: 10.1105/tpc.1.9.839
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of beta-glucuronidase expression in transgenic tobacco plants by an A/T-rich, cis-acting sequence found upstream of a French bean beta-phaseolin gene.

Abstract: A 0.8-kilobase fragment from the 5'-flanking region of a French bean beta-phaseolin gene yielded strong, temporally regulated, and embryo-specific expression of beta-glucuronidase (GUS) in transgenic tobacco plants, paralleling that found for the seed protein phaseolin [Sengupta-Gopalan, C., Reichert, N.A., Barker, R.F., Hall. T.C., and Kemp, J.D. (1985) Proc. Natl. Acad. Sci. USA 82, 3320-3324]. Gel retardation and footprinting assays using nuclear extracts from immature bean cotyledons revealed strong bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…Further, one Myb and two Myb-like recognition sites, and one sequence which closely resembles an ABA-inducible Sph-containing element or Sph box (ASCE), which is conserved in many seedspecific promoters (Hattori et al 1992), were identified (Table 1). Two regions rich in A/T are located between À539 and À424 bp, and they may act as general enhancers of gene expression (Bustos et al 1989). We also identified the sequence of the PB core motif, which is present in promoters of pollen-specific genes of tomato (Twell et al 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, one Myb and two Myb-like recognition sites, and one sequence which closely resembles an ABA-inducible Sph-containing element or Sph box (ASCE), which is conserved in many seedspecific promoters (Hattori et al 1992), were identified (Table 1). Two regions rich in A/T are located between À539 and À424 bp, and they may act as general enhancers of gene expression (Bustos et al 1989). We also identified the sequence of the PB core motif, which is present in promoters of pollen-specific genes of tomato (Twell et al 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Data are shown as the mean of at least three independent measurements and error bars indicate the SE the naturally desiccation-tolerant tissues pollen and seeds (specifically embryos; Cuming 1999; Bartels 1999), which supports a role for these proteins in desiccation. Previous studies of seed-specific genes have shown that A/T-rich sequences in the promoter can act as general enhancers of seed specific expression (Bustos et al 1989). Such sequences are present in the CpEdi-9 promoter and could promote expression in seeds.…”
Section: Discussionmentioning
confidence: 99%
“…β-phaseolin promoter from bean is another promoter of described activity (Bustos et al 1989). β-1,3-glucanase promoter from peas (PsGNS2) is an interesting example of seed-specific construct, as it provides transgene expression in the seed coat.…”
Section: Time-specific Promotersmentioning
confidence: 99%
“…Phaseolin is the major SSP of bean. Phaseolin (phas) gene expression is temporally and spatially regulated and is completely inactive during the vegetative phase of plant development (Bustos et al, 1989;van Der Geest et al, 1995). Silencing of the phas gene in vegetative tissues was associated with the presence of a nucleosome positioned over the three phased TATA boxes present in the phas promoter (Kadosh & Struhl, 1998).…”
Section: Epigenetic Regulation Of Seed Maturationmentioning
confidence: 99%